A Conceptual Schema Based XML Schema with Integrity Constraints Checking - Oviliani Yenty Yuliana; Suphamit Chittayasothorn (My University, 2008)
The more popular XML for exchanging and representing information on Web, the more important flat XML (XML) and intelligent editors become. For data exchanging, an XML data with an XML Schema and integrity constraints are preferred. We employ an object-role modeling (ORM) for enriching the XML Schema constraints and providing better validation the XML Data. An XML conceptual schema is presented using the ORM conceptual model. Editor Meta Tables are generated from the conceptual schema diagram and are populated. A User XML Schema base on the information in the editor meta tables is generated. However, W3C XML Schema language does not support all of the ORM constraints. Therefore, we propose an Editor XML Schema and an Editor XML Data to cover unsupported the ORM constraints. We propose the algorithms for defining constraint in the User XML Schema and extending validity constraint checking. Finally, XQuery is used for extending validity checking.
Keywords: RELAX NG; XML Schema (W3C); Advanced Database Systems and Queries